2023
DOI: 10.1021/acs.jpcb.3c06297
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Lipid Eutectics Using Coarse-Grained Molecular Dynamics

Robert J. Cordina,
Beccy Smith,
Tell Tuttle

Abstract: Binary triacylglyceride (TAG) systems are known to exhibit nonlinear/eutectic behavior, and predicting this is not straightforward unless the thermodynamic properties of the constituent TAGs are known. While this kind of behavior has been shown previously using molecular dynamics, this was carried out using an atomistic force field and fully saturated symmetric TAGs. In this study, we simulate the changing melting point of binary unsaturated asymmetric TAG systems using a coarse-grained force field. While the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The most recent paper by this group has extended this methodology further to binary systems of sn ‐POSt, sn ‐POP, and sn ‐StOSt (Cordina et al., 2023c). Using similar methodology as in their previous paper to determine the melting point of a single TAG‐type crystal (Cordina et al., 2023a), the COGITO forcefield was tested to determine whether it could be used to determine the nonlinear behavior of such binary systems.…”
Section: Molecular Dynamics Simulations Applied To Tagsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent paper by this group has extended this methodology further to binary systems of sn ‐POSt, sn ‐POP, and sn ‐StOSt (Cordina et al., 2023c). Using similar methodology as in their previous paper to determine the melting point of a single TAG‐type crystal (Cordina et al., 2023a), the COGITO forcefield was tested to determine whether it could be used to determine the nonlinear behavior of such binary systems.…”
Section: Molecular Dynamics Simulations Applied To Tagsmentioning
confidence: 99%
“…Using similar methodology as in their previous paper to determine the melting point of a single TAG‐type crystal (Cordina et al., 2023a), the COGITO forcefield was tested to determine whether it could be used to determine the nonlinear behavior of such binary systems. The authors showed that, although the simulated melting points of the binary mixtures at various ratios were generally found to be lower than those determined empirically, the overall nonlinearity of the systems was reproduced well, such as the eutectic point of sn ‐POP/ sn ‐POSt at a 50:50 ratio and sn ‐POP/ sn ‐StOSt at a 80:20 ratio (Cordina et al., 2023c).…”
Section: Molecular Dynamics Simulations Applied To Tagsmentioning
confidence: 99%